Understanding and Assessing the Motivation Factors of University Students’ Involvement in Volunteerism. - Lukman@Zawawi, Mohamad; Azlini, Chik; Normala, Riza (2018)
Volunteerism is one of the areas that is increasingly gaining attention in improving capabilities among students in Malaysia. Volunteering activity is such a noble work that able to give value to human development and improving social skills. Hence, it is crucial to this research to identify the factors of student involvement in volunteerism. Information were collected at a University Sultan Zainal Abidin among the members of student's volunteer organization that involved 210 respondents. This study used quantitative method and all the information obtained were conducted through survey. The results showed that factor gaining a reward or honor found to be negatively related to volunteer and other factors were positive related to the volunteer. The Ministry of Higher Education should ensure that volunteering is always raised as a living culture amongst students and nurtured within them. Hence, it can be developed the soul to sympathy and courtesy, harmonize the community with concern and affection in the pursuit of sustainable community development.